Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

Pages: **1**

**mathematics7****Member**- Registered: 2013-04-02
- Posts: 2

Prove that the error of the Gaussian quadrature rule is

(integral of f (x)dx from a to b dx) - (∑ ie sum from i=1 to n of ci f(xi) = ((f^(2n)(z))/(2n)!)(integral of (∏ ie sum of products from i =1 to n of (x - xi)^2) from a to b dx)

for some z element of (a, b). Hint: Consider some kind of interpolation of f .

It would be nice if you could provide a clear proof so I could understand the error of the Gaussian quadrature rule.

Offline

Pages: **1**